Recent Advances in Implantable 3D-Printed Scaffolds for Repair of Spinal Cord Injury - Salar Khaledian; Ghobad Mohammadi; Mohadese Abdoli; Arad Fatahian; Arya Fatahian; Reza Fatahian (Advanced Pharmaceutical Bulletin)
Spinal cord injury (SCI) is an important factor in sensory and motor disorders that affects thousands of people every year. Currently, despite successes in basic science and clinical research, there are few effective methods in the treatment of chronic and acute spinal cord injuries. In the last decade, the use of 3D printed scaffolds in the treatment of SCI had satisfactory and promising results. By providing a microenvironment around the injury site and in combination with growth factors or cells, 3D printed scaffolds help in axon regeneration as well as neural recovery after SCI. Here, we provide an overview of tissue engineering, 3D printing scaffolds, the different polymers used and their characterization methods. This review highlights the recent encouraging applications of 3D printing scaffolds in developing the novel SCI therapy.